ADAPTASI KOSAKATA BAHASA BALI DALAM BAHASA MELAYU LOLOAN BALI - Anak Agung Putu; Ni Luh Nyoman Seri; I Nyoman Suparwa (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2015)
AbstractThis study aims to describe processes and domains of vocabulary borrowing, wordcategories, and phonological dynamics in the Loloan Malay language in Bali. The datawere collected through participant observations and were analyzed using the generativephonological theory. The results of the study are as follows. First, the Loloan Malaylanguage borrows Balinese vocabulary through two processes, namely adoption andadaptation. Second, the borrowing of Balinese vocabulary in terms of seven universalcultural elements covers the domains of livelihood system, technology, knowledge system,organization, and arts. Third, the borrowing of Balinese vocabulary in terms of wordcategories occurs in: (a) nouns, pronouns, and numerals; (b) verbs; and (c) adjectives.Fourth, the borrowing of Balinese vocabulary results in the phonological dynamics inthe Loloan Malay language.Keywords: borrowing domains